Secure and Reliable Localization in Wireless Sensor Network Based on RSSI Mapping - Pyda, Jakub; Prokop, Wojciech; Rusinek, Damian; Ksiezopolski, Bogdan (Computer Networks, 2017)
The growing number of mobile devices and the popularity of Internet of Things (IoT) applications have caused an increase of local-area location-aware protocols and applications. Localization has become a popular topic in the literature and many localization algorithms in wireless sensor networks (WSN) have been proposed. However, the most of them are vulnerable to common wireless attacks. In this article, we introduce the secure localization protocol based on a RSSI-mapping, which uses symmetric cryptography. The security attributes of the protocol have been proved using the Scyther tool. We present the experimental results that demonstrate the ability to estimate sensor’s location in the environment, where other networks are available. The results show, that the introduction of security mechanisms to localization protocols may significantly increase the execution time and exceed strict time restrictions in some real-time applications. Nevertheless, the existence of insecure protocol in hostile environment is unacceptable. To achieve a better efficiency, we suggest to use the hardware encryption provided in CC2420 radio chip.